Decentering the cold war in Southern Africa: the portuguese policy of decolonization and détente in Angola and Mozambique (1974–1984) - Reis, B. C. (Journal of Cold War Studies, 2019)
Contrary to the expectations of many, the break between Portugal and its former colonies in southern Africa was far from complete after decolonization. This article points to three major reasons. First, the impact on relations with Angola and Mozambique of the fragmentation of Portuguese state power and tense polarization in the Portuguese polity after the military coup of 24 April 1974 has been overstated and was far from entirely negative. Second, diplomatic relations were normalized between Portugal, Angola, and Mozambique during the Cold War in a way that has significant parallels with West Germany's Ostpolitik. Portugal's Südpolitik saw a cultural identity worth preserving despite geopolitical divisions and pushed for better relations and deepened ties with these states to help move them away from strict alignment with the Soviet bloc. Third, officers of the Armed Forces Movement that carried out the April 1974 coup exercised a fundamental, positive influence in Portuguese policies toward Angola and Mozambique during decolonization and for years afterward.